Auditing the Governance and Management of Green IT. Issue 5 (3rd September 2022) - Patón-Romero, J. David; Baldassarre, Maria Teresa; Toval, Ambrosio; Rodríguez, Moisés; Piattini, Mario
ABSTRACT: Sustainability is not a trend; more and more areas of knowledge defend it and apply it among their main characteristics. The area of Information Technology (IT) has not been left behind and, through the so-called Green IT, advocates for a more sustainable environment. Organizations around the world are realizing that Green IT is an important asset that produces great benefits at ecological, social, and economic level. For this reason, we have developed a revised version of the "Governance and Management Framework for Green IT" . With this new version we intend to offer a more complete and solid guide that helps organizations to gradually implement, assess, and improve those characteristics of governance and management that are the basis of the processes and practices of Green IT. This proposal has been empirically validated through a case study and the results obtained demonstrate the validity, usefulness, and applicability of the framework for organizations.